Aktivitas Antibakteri Ekstrak Daun Jarak Pagar (Jatropha Curcas L) Terhadap Staphylococcus Epidermidis Dan Staphylococcus Aureus Secara In Vitro - Susilo Yulianto; Sunarmi Sunarmi (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract: Jatropha Leaves, Staphylococcus Epidermidis, Staphylococcus Aureus. Jatropha curcas L leaves contain tannins, saponins and flavonoids. According to some studies, tannins, saponins and flavonoids have antibacterial power. Based on these indications, it is important to do research on antibacterial potency of jatropha leaf extract (Jatropha curcas L) against Staphylococcus epidermidis and Staphylococcus aureus bacteria. The aim of this research is to know Antibacterial Activity of Jatropha curcas L Extract on Staphylococcus epidermidis and Staphylococcus aureus". This research. An experimental study by testing the antibacterial activity of leaf extract and jatropha result of maceration, infundation and reflux as measured by Minimal Inhibitory Concentration (KHM) on growth of Staphylococcus epidermidis and Staphylococcus aureus bacteria. From the results of the research, it was found that the extract of the reflux was brownish green and the characteristic of jatropha leaves. The amount of extract produced was 17.03 g, so the yield was 17.03%. Jatropha leaf extract of maceration has no inhibitory power to S. epidermidis in 4 series concentrations starting from 3.125 ppm to 25.000 ppm. Inhibitory zones begin to appear at concentrations of 50,000 ppm and increase at concentrations of 100,000 ppm. The drag zone diameter in the Jatropha curcas extract of the reflux showed the inhibitory power in all series of concentrations. The smallest inhibitory zone was shown at a concentration of 3,125 ppm (9.33 mm) and increased with increasing concentrations. The diameter of the inhibit zone was greatest at 100,000 ppm concentrations of 22.67 mm. Description of inhibitory zone diameter of methanol leaf extract of jatropha result of maceration and reflux to S. epidermidis. The conclusion of this research is extract of reflux result giving bigger resistance than maceration extract to S. epidermidis and S. aureus. Methanol extract of jatropha from the maceration and reflux have strong antibacterial activity against S. epidermidis and S. aureus but still under Klindamycin.